Carving intracrater layered deposits with wind on Mars. Issue 6 (31st March 2016) - Day, M.; Anderson, W.; Kocurek, G.; Mohrig, D.
Abstract: Crater basins on Mars host thick sedimentary sequences, which record the environments of early Mars. These basin fills commonly exhibit mound morphologies thought to arise from aeolian erosion of initially crater filling strata. This study presents transport‐based models explaining how mounds could be carved by wind. Wind tunnel experiments generated morphologies similar to those observed on Mars, and numerical modeling of flow over a crater using large‐eddy simulation (LES) demonstrated a positive feedback between topographic focusing of flow and erosion potential. Observations of yardangs, dunes, and wind streaks, all proxies for wind direction, largely agree with model results. Where mound strata origins have been interpreted, basal subaqueous deposits are overlain by aeolian deposits. This stratigraphic progression, culminating in wind‐driven excavation, is consistent with a global desiccation event. The occurrence of sedimentary mounds only on Noachian terrain argues that this event was related to late Noachian climatic change. Key Points: Experiments and numerical model affirm aeolian erosion carved intracrater deposits into mounds Distribution of intracrater mounds supports a global desiccation event in early Martian history Craters have transitioned from sediment sinks in the Noachian to sediment sources on modern Mars